Dominance of the Beijing genotype among XDR Mycobacterium tuberculosis strains in Russia. (March 2015) - Vyazovaya, A.; Mokrousov, I.; Zhuravlev, V.; Solovieva, N.; Otten, T.; Vishnevsky, B.; Narvskaya, O.
Abstract: Introduction: The emergence and spread of multidrug-resistant and, more recently, extensively-drug resistant tuberculosis (MDR-TB and XDR-TB) is a major concern of public health that hampers efficient TB control. The Mycobacteriology Laboratory in the St. Petersburg Research Institute of Phthisiopulmonology serves as a reference center for northwest Russia (11 provinces; 1, 700, 000 sq. km; population of 13.5 million); additionally, the laboratory receives strains from other regions across Russia. This study aimed to perform a molecular characterization of XDR Mycobacterium tuberculosis isolates recovered from TB patients in northwestern Russia during the time period of 2011–2013. Materials and methods: M. tuberculosis isolates from mainly pulmonary TB patients (extrapulmonary TB, n  = 7) were identified and characterized using traditional biochemical methods, including susceptibility testing for 11 anti-TB drugs (streptomycin, isoniazid, rifampin, ofloxacin, kanamycin, amikacin, capreomycin, ethambutol, ethionamide, pyrazinamide, and PAS acid). Drug susceptibility testing (DST) was done using a method of absolute concentrations according to the guidelines of the Russian Ministry of Health (order No. 109 of 21 March 2003) and/or BACTEC MGIT 960 system according to the manufacturer's recommendations. Extensive drug resistance was defined as recommended by WHO (World Health Organization) as resistance to isoniazid and rifampin (MDR) plus resistance to one of the fluoroquinolones and one of three injectable drugs (kanamycin, amikacin, capreomycin). The isolates were further subjected to spoligotyping followed by comparison with SITVIT_WEB and MIRU-VNTRplus databases. LAM family was defined by Rv0129c SNP analysis. Results: A total of 115 XDR M. tuberculosis isolates were included in this study. They presented 41 different patterns of drug resistance. XDR was complemented with resistance to streptomycin ( n  = 114), and/or ethambutol ( n  = 93), ethionamide ( n  = 80), pyrazinamide ( n  = 43), or PAS acid ( n  = 40). Of the three injectable drugs, XDR was mainly due to kanamycin resistance alone ( n  = 39, 34%), followed by combined kanamycin and amikacin resistance ( n  = 13), amikacin and capreomycin resistance ( n  = 11), kanamycin and capreomycin resistance ( n  = 9). Spoligotyping assigned the isolates to 3 genetic families: Beijing (98; 87%), LAM (SIT42, n  = 6; SIT252, n  = 2; SIT496, n  = 2) and Ural (SIT262, n  = 7). SIT1 was predominant among Beijing isolates. The proportion of isolates resistant to any of 5 drugs (including, streptomycin, isoniazid, rifampin, ofloxacin and/or kanamycin, amikacin, and capreomycin) was 1.7% ( n  = 2), to 6 drugs – 7.8% ( n  = 9), to 7 drugs – 19.1% ( n  = 22), to 8 drugs – 26.9% ( n  = 31), to 9 drugs – 25.2% ( n  = 29), to 10 drugs – 12.1% ( n  = 14). Eight isolates of the Beijing genotype were resistant to all 11 tested drugs. Conclusions: XDR M. tuberculosis population in northwestern Russia is heavily dominated by Beijing genotype isolates (87%). Acknowledgements: Russian Science Foundation (Grant agreement 14-14-00292).